Perilaku Inovatif: Peran Kepemimpinan Transformasional dan Keterlibatan Kerja - Shivana Diva Nur Maya; Anwar Mansyur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to examine the influence of transformational leadership and work involvement on innovative behavior. The research method used is quantitative research. Data collection for this research used a questionnaire given to all employees of PT. Mapan Wijaya Demak. The population in this study were employees of PT Mapan Wijaya Demak with a sample of 105 respondents. The sampling method in this research used non-probability sampling with census sampling technique (saturated sampling). The data collection technique uses a questionnaire and data processing is assisted by SPSS (Statistical Products for Service) software. The results of this research show that transformational leadership and work involvement have a positive and significant effect on innovative behavior. In conclusion, there is an influence of transformational leadership and work involvement in innovative behavior Keywords : Inovatif Behavior, Transformational Leadership, Work Involvement